The democracy paradox, and some of its moral and legal implications - Şenol, Hüseyin Fırat. (Thesis (M.A.) - Bogazici University. Institute of Social Science, 2002., 2002)
The thesis focuses on showing that it is not a paradox of democratic governments to use sanctions on individuals whose actions are conducive to increasing rebellion and uncivilised behaviour in the society, and on those who aim at destroying democracy, that is, the political and legal basis for the furthering and enjoyment of liberties and rights. It furthermore aims at giving an explanation of the moral foundations of free society by appealing to Kant and Mill. The discussion on whether or not democracy contradicts itself by using sanctions on individuals who abuse their liberties and rights in order to deprive others of theirs will also be a response to historicists, who claimed that democracy has to copy totalitarian methods to fight against its alternatives, and to become totalitarian itself. In the legal implications part, Rawls and Oliver W. Holmes will be used as bases to give criteria for udging how the elected may abuse the executive power on one hand, and, what type of actions go beyond the scope of basic liberties and rights on the other.
Keywords: Democracy.; Liberty.